A general solution for distorted flows in aerofoil cascades and contributions to distortion sensitivity reductions - El-Attar, M. A. R. A. A. (Cranfield University, 1975)
This thesis presents a number of new solutions to reduce the sensitivity of an existing compressor stage to a specified inlet flow distortion._ The interacting effects of flow vorticity, the change of rotor incidence and the time rate of change of íncidence are then studied, yielding a new design criterion to reduce the sensitivity of a compressor stage to any circumferential inlet flow maldistribution. Furthermore, the application of the unsteady thin a stator or inlet guide vane and a rotor, results unsteady fluctuating lift function which contains .functions as special cases. - Minimisation of the aerofoil theory to inia new generalised Sears and Hor1ock's resultant fluctuating ' lift leads to a design criterion for inlet guide vanes in agreement with the above conceptwhich is obtained by a different approach. The thesis also discusses a number of possible mathematical models for Cascade shear flow investígating their advantages and disadvantages and'the possibilities°of obtaining solutions. gA linearised theory for-_ nonuniform cascade flow is presented.i This fs'main1y an extension of Schlichting's method,`ref;(27) for uniform flow,i ' The main contribution of this work is the development of a nonlinear theory for nonuniform~cascade shear flow.â The.theory-accepts large amplitudes of distortion of any smooth shape, that is, cusps and 'g sharp corners in the Velocity distribution should be rounded. It is also capable of treating cascades of thick and highly cambered blades. The solution of Poisson's equation is obtained in the form of Fredholm'sV integral equation of the second kind which reduces to Martensen's equations, ref.(29), when the vorticity is zero everywhere in the flow field (clean flow). .The vorticity transport equation is satisfied in the flow field and its simultaneous solution with the solution of Poisson equation is carried out through an iteration process. Good agreement is obtained between the theoretical predictions and experimental test result